2021
DOI: 10.1186/s12870-021-03318-6
|View full text |Cite
|
Sign up to set email alerts
|

The bHLH transcription factor AhbHLH112 improves the drought tolerance of peanut

Abstract: Background Basic helix-loop-helix (bHLH) transcription factors (TFs) are one of the largest gene families in plants. They regulate gene expression through interactions with specific motifs in target genes. bHLH TFs are not only universally involved in plant growth but also play an important role in plant responses to abiotic stress. However, most members of this family have not been functionally characterized. Results Here, we characterized the fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 86 publications
(69 reference statements)
0
31
0
Order By: Relevance
“…Plants have evolved complex regulatory hormonal signaling networks to respond and adapt to drought conditions. ABA has emerged as a crucial regulator of the drought response (C. Li et al ., 2021; J. Li et al ., 2021; Q. Li et al ., 2021). bHLH TFs are involved in regulating ABA signaling to help plants cope with drought stress (Hao et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Plants have evolved complex regulatory hormonal signaling networks to respond and adapt to drought conditions. ABA has emerged as a crucial regulator of the drought response (C. Li et al ., 2021; J. Li et al ., 2021; Q. Li et al ., 2021). bHLH TFs are involved in regulating ABA signaling to help plants cope with drought stress (Hao et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that the overexpression of SBP family proteins imparts abiotic tolerance to different plants [ 44 ]. bHLH family protein was identified as a homologue of TraesCS2D02G000200 in Utricularia gibba and Phytochrome interacting factor 3-like 6 which is one of the bHLH family proteins was found as a homologue of the same gene in Arabidopsis thaliana [ 45 ]. Characterize the function of a bHLH transcription factor (AhHLH112) in drought conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Results depicted these genes remarkably retaliated to water deficit and ABA in roots and/or leaves. The work was useful in directing the useful depiction and enhanced drought-resilient germplasms in peanuts (Li et al, 2021). Heterologous overexpression of Arabidopsis ANAC042/AtJUB1 in tomato (S. lycopersicum) and Arabidopsis enhanced abiotic stress resilience in these plants (Alshareef et al, 2019).…”
Section: Nac Tfsmentioning
confidence: 99%